The Ability in Constructing WH-Questions by the First Year Students of SMP Negeri 10 Kupang in the Academic Year 2022/2023 - Agnes Manek; Rudolof Jibrael Isu (English Education Postgraduate Program, Universitas Negeri Manado, 2022)
This study was conducted to find out the students’ mastery level in constructing WH-Questions and find out the difficulties faced by the first year students of SMP N. 10 Kupang in constructing questions by using WH-Questions. A Descriptive Quantitative Method was employed to describe the two answers. A class of the first year students of SMP N. 10 Kupang consisting of 31 students were taken as the sample of this research. The instrument of this research was a test of Multiple Choice (30 items) and Completion (20 items). The result of the research shows that the first year students of SMP N. 10 Kupang have not perfectly mastered yet the English WH-Questions, as shown in the result of the discussion. The average percentage of the students’ mastery level is 69,9%. So according to Arikunto’s standard measurement, this percentage is categorized into “Average Level” (Arikunto, 1998 : 226). The highest percentage of the students’ mastery level in constructing WH-Questions is 74,7% for WH-Question “Who”, whereas the lower percentage is 57,1 for WH-Question “How”. The most difficult problem encountered by the students in doing the test caused they could not differentiate the WH-Questions one from another, for example they use “Who” instead of “What”. The difficulties face by the students in doing the test is caused by the students’ misunderstanding on the rules (the English grammar), their lack of knowledge of WH-Questions and also caused by the inter lingual error where the students influenced by their mother tongues.